Programmable Logic Controller - Affonso Guedes, Luiz (IntechOpen, 2010)
Despite the great technological advancement experienced in recent years, Programmable Logic Controllers (PLC) are still used in many applications from the real world and still play a central role in infrastructure of industrial automation. PLC operate in the factory-floor level and are responsible typically for implementing logical control, regulatory control strategies, such as PID and fuzzy-based algorithms, and safety logics. Usually PLC are interconnected with the supervision level through communication network, such as Ethernet networks, in order to work in an integrated form. In this context, this book was written by professionals that work and research in automation area and it has two major objectives. The first objective is present some advances in methodologies and techniques for development of industrial programs based on PLC. The second objective is present some PLC-based real applications from various areas such as manufacturing system, robotics, power system, communication system, and education.